Quadratic geometric transformation generated by ball mappings and its applications - Bektybaeva, Зияш (Рroblems of engineering and professional education, 2023)
In this article, a new type of quadratic transformation is studied and proposed for use in graphic geometry. It is recommended to use the turbine blade for geometric modeling